Dampak Kendala Teknis QRIS BSI terhadap Kelancaran Usaha dan Kepuasan UMKM di Kampus Inggris Pare - Denta Cahya Regita; Fibrianis Puspita Anhar (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: Some business owners in Kampung Inggris Pare use BSI QRIS for accepting payments, but in practice, technical obstacles often arise that disrupt the smoothness of transactions. Research Methods: The study used a qualitative field approach with interviews, observations, and documentation of fifteen MSME owners and two BSI KCP Kediri Pare Supratman staff. Results: The results showed that the most frequently encountered obstacles were delays in payment notifications, funds not arriving in real time, and internet network disruptions. These obstacles impacted daily cash flow disruptions, long queues, and decreased user satisfaction with BSI QRIS services. BSI responded to these obstacles through customer service, merchant assistance, and education on application usage, although it was not able to eliminate all obstacles experienced by users in the field. Conclusion: BSI's QRIS system, using the Byond application, continues to experience technical issues that disrupt business continuity and user satisfaction. BSI's efforts to address these issues have not fully resolved them.